The distribution and bionomics of anopheles malaria vector mosquitoes in Indonesia. - Elyazar, I; Sinka, M; Gething, P; Tarmidzi, SN; Surya, A; Kusriastuti, R; Winarno; Baird, J; Hay, S; Bangs, M (2013)
Malaria remains one of the greatest human health burdens in Indonesia. Although Indonesia has a long and renowned history in the early research and discoveries of malaria and subsequently in the successful use of environmental control methods to combat the vector, much remains unknown about many of these mosquito species. There are also significant gaps in the existing knowledge on the transmission epidemiology of malaria, most notably in the highly malarious eastern half of the archipelago. These compound the difficulty of developing targeted and effective control measures. The sheer complexity and number of malaria vectors in the country are daunting. The difficult task of summarizing the available information for each species and/or species complex is compounded by the patchiness of the data: while relatively plentiful in one area or region, it can also be completely lacking in others. Compared to many other countries in the Oriental and Australasian biogeographical regions, only scant information on vector bionomics and response to chemical measures is available in Indonesia. That information is often either decades old, geographically patchy or completely lacking. Additionally, a large number of information sources are published in Dutch or Indonesian language and therefore less accessible. This review aims to present an updated overview of the known distribution and bionomics of the 20 confirmed malaria vector species or species complexes regarded as either primary or secondary (incidental) malaria vectors within Indonesia. This chapter is not an exhaustive review of each of these species. No attempt is made to specifically discuss or resolve the taxonomic record of listed species in this document, while recognizing the ever evolving revisions in the systematics of species groups and complexes. A review of past and current status of insecticide susceptibility of eight vector species of malaria is also provided.